2017
DOI: 10.1038/s41598-017-02588-1
|View full text |Cite
|
Sign up to set email alerts
|

Difference in Cerebral Circulation Time between Subtypes of Moyamoya Disease and Moyamoya Syndrome

Abstract: In this study, we evaluated the differences in hemodynamics between hemorrhagic and non-hemorrhagic moyamoya disease (MMD) and moyamoya syndrome (MMS) by measuring cerebral circulation time (CCT). This case-control study included 136 patients with MMD or MMS diagnosed between April 2015 and July 2016 at Beijing Tian Tan Hospital. Each hemisphere was analyzed separately. The difference in clinical, radiological characteristics and CCT between subtypes of MMD and MMS were analyzed statistically. The results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…This suggests that an increased cerebral circulation time in multiple patients with sclerosis corresponds to microvascular dysfunction [ 20 ]. Another study has revealed differences in cerebral circulation time between patients with hemorrhagic and non-hemorrhagic moyamoya disease [ 21 ]. Cerebral circulation time of the contrast may vary depending on the degree of cerebral perfusion in the brain parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that an increased cerebral circulation time in multiple patients with sclerosis corresponds to microvascular dysfunction [ 20 ]. Another study has revealed differences in cerebral circulation time between patients with hemorrhagic and non-hemorrhagic moyamoya disease [ 21 ]. Cerebral circulation time of the contrast may vary depending on the degree of cerebral perfusion in the brain parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…Hemorrhagic stroke is one of the main factors leading to worse prognosis, and occurs mainly owing to the rupture of abnormally contribute to decreasing the risk of rebleeding in patients with hemorrhagic MMD (13,17,18,21). However, with the establishment of artificial collateral vessels and the regression of original collateral vessels, how the cerebral hemodynamics changes in hemorrhagic MMD after surgical revascularization is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that intracranial hemorrhage occurs mainly owing to the rupture of abnormal moyamoya vessels, dilated collateral vessels, and complicated aneurysms (13)(14)(15). Revascularization surgery was supposed to decrease the intravascular pressure load of original collaterals in internal carotid artery (ICA) system and alleviate the dilation of collateral vessels or complicated aneurysms, which may contribute to decrease the risk of rebleeding in patients with hemorrhagic MMD (13,17,18,(26)(27)(28). However, there has been much controversy with respect to the most appropriate surgical method and outcome of hemorrhagic MMD.…”
Section: Discussionmentioning
confidence: 99%